Characterization of the Microbial Flora from Suan Yu, a Chinese Traditional Low‐Salt Fermented Fish. Issue 5 (18th December 2015) - Zeng, Xuefeng; Chen, Xiaohua; Zhang, Wei
Abstract: The microbial flora of naturally fermented Suan yu was investigated by phenotype combined with gene analysis at different stages of fermentation. Results shows that lactic acid bacteria (LAB) and yeast were gradually increased during fermentation and the counts were ripening to 7.93–8.56 and 5.14–5.75 log cfu/g, respectively, at the end of the fermentation. Staphylococci gradually increased during the first fermentation stage and then slowly decreased until the end of ripening (4.13–4.92 log cfu/g). Majority of the LAB isolated from Suan yu were L actobacillus plantarum and P ediococcus pentosaceus, followed by L euconostoc and L actobacillus paralimentarius species. The yeast mainly consisted of S accharomyces cerevisiae and H ansenula anomala . The predominant S taphylococcus isolated from Suan yu comprised S taphylococcus saprophyticus and S taphylococcus xylosus . The main microorganism in early fermentation included Leuconostoc mesenteroides, P seudomonas and Enterobacteriaceae and the followed subsequent stage included L . plantarum, P . pentosaceus, S . xylosus, S . saprophyticus, S . cerevisiae and H . anomala . Practical Applications: In this study, the specific microorganisms and their microbial dynamics were investigated during Suan yu fermentation. Results showed that lactic acid bacteria, coagulase‐negative Staphylococci and yeat were predominant microorganisms during the ripening fermentation. Therefore, these predominant organisms are responsible for the Suan yu unique flavor, taste, color and ensure their safety. Furthermore, selecting the most appropriate autochthonous microflora as starter formulation can effectively preserve the typical characteristics of the Suan yu.